Mixtec taxonomy: plant classification, nomenclature, and identification in Oaxaca, Mexico - Aparicio, Juan Carlos; Voeks, Robert; Funch, Ligia (Ethnobotany Research and Applications, 2021)
Background: Ethnotaxonomy seeks to understand how members of a culture name and categorize biological organisms in their local language. This research examined the ethnotaxonomy of plants among the Mixtec people in the municipality of San Miguel el Grande, Oaxaca, Mexico. Methods: We conducted a collaborative research between 2019 and 2020 with 42 Mixtec men and women between 38 and 100 years of age, in the ten communities that make up the municipality. We focused on classification, nomenclature and plant identification. Results: There is a more or less hierarchical classification that contemplates both cognitive and utilitarian aspects. The nomenclature shows that the Mixtec of the study area have taken into account the characteristics of the plants—cultural, experiential, and ecological—to name them. Identification is based on multiple morphological, ecological, cultural and experiential mechanisms. Conclusion: The botanical ethnotaxonomy of San Miguel el Grande is rich and varied, revealing that plants play an important role in the lives of people. However, it seems that the disuse of some plants and the Spanish language is conditioning the maintenance of Mixtec plant names. Keywords: Folk taxonomy, Mixtec region, ethnobotany, Mixtec language, ethnotaxonomy.